7 - Commerce et système d’information : le cas des vendeurs de pagnes à Brazzaville (Congo)* - Ndinga, Mathias Marie A. (Africa Development, 2007)
This paper seeks to establish the impact of information and communication tech- nologies (ICTs) on the trade in wrapper cloth in Brazzaville, Congo. The study focused on access, use and impact and concluding that the level of access is low in general and for men and women taken separately, although men have more access than women. There is very little evidence of ICT use in dealings between consumer and traders (wholesalers and retailers alike). There is significant difference in ICT use between men who have mobile phones on the one hand, and between men and women on the other hand. Among traders in wrapper cloth, the proportion who perceive access to ICT as beneficial to the gains they make is low. Results are more encouraging amongst men than women, with econometric analysis showing a significant impact of ICTs on daily earnings in dealings with suppliers. Finally, the policy is to encourage widespread use of ICTs by the popu- lation in general, and by wrapper cloth traders in particular.